Uji Potensi Antibakteri Isolat Rare Actinomycetes Material Pasir Pantai Baron Gunung Kidul Yogyakarta terhadap Bakteri Pseudomonas aeruginosa - Fatoni, Jauhar, Ratna Yuliani, M.Biotech.St (2016)
The resistance of bacteria causes most antibiotics ineffective. The new antimicrobial agents are needed to cope with the increasing number of antibiotic-resistant bacteria. Rare Actinomycetes, an Actinomycetes strain, is a part of the potential as producers of bioactive compounds including antibiotic compounds. The purpose of this study was to obtain rare Actinomycetes isolates from beach sand material taken from Baron Gunung Kidul in Yogyakarta and potentially antibacterial against Pseudomonas aeruginosa. The research included pre-treatment samples of sand by the method of dry heat at a temperature of 120 ° C for 1 hour, then the isolation of rare Actinomycetes with starch-casein agar, Bennett agar, and oatmeal agar, and identify the microscopic and the macroscopic and the latter is the screening of antibacterial activity against Pseudomonas aeruginosa with agar block method. Based on the results, the 18 isolates from sand beach Baron Gunung Kidul suspected as rare Actinomycetes. Isolates rare Actinomycetes strain codes 3A and 1M has a weak potential to inhibit the bacteria Pseudomonas aeruginosa with inhibition zone diameter 8 mm and 11.5 mm. Keywords: Antibacterial, Pseudomonas aeruginosa, rare Actinomycetes